1996
DOI: 10.1164/ajrccm.153.1.8542156
|View full text |Cite
|
Sign up to set email alerts
|

Black spots concentrate oncogenic asbestos fibers in the parietal pleura. Thoracoscopic and mineralogic study.

Abstract: Epidemiologic and pathologic data demonstrate that malignant mesothelioma occurs preferentially after exposure to long amphibole asbestos fibers. However, mineralogic studies have rarely detected such fibers in the parietal pleura. We hypothesized that the distribution of asbestos fibers in the pleura was heterogeneous and that they might concentrate in certain areas, as does coal dust in patients showing anthracotic "black spots" of the parietal pleura during thoracoscopy. We collected thoracoscopic biopsy sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
125
0
4

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(135 citation statements)
references
References 19 publications
5
125
0
4
Order By: Relevance
“…The pathways through which fibers reach the pleura, and the populations and sizes of fibers that are responsible for this proliferation, are presently unknown. Our finding of site-specific mesothelial cell proliferation in the rodent parietal pleura strongly supports the recent observation of Boutin and colleagues (16), who found that asbestos fibers accumulate in specific sites in the human parietal pleura associated with lymphatic drainage.…”
Section: Discussionsupporting
confidence: 92%
“…The pathways through which fibers reach the pleura, and the populations and sizes of fibers that are responsible for this proliferation, are presently unknown. Our finding of site-specific mesothelial cell proliferation in the rodent parietal pleura strongly supports the recent observation of Boutin and colleagues (16), who found that asbestos fibers accumulate in specific sites in the human parietal pleura associated with lymphatic drainage.…”
Section: Discussionsupporting
confidence: 92%
“…Dodson et al 4) , found asbestos fibers (predominantly chrysotile) in pleural hyaline plaque taken from 8 cases of shipyard workers. Boutin et al 24) , also found highly concentrated asbestos fibers in black spots (glomerate lymphatic capillaries stained dark due to anthracotic pigmentation) in the parietal pleura. They said that amphibole outnumbered chrysotile in the black spots.…”
Section: Commentsmentioning
confidence: 90%
“…Asbestos fibers have been identified in the pleura by autopsy, chrysotile being the predominant asbestos form found in pleural plaques [51] and pleural/mesothelial tissues in general [46,52]. In a singular contradicting report amphibole fibers outnumbered chrysotile ones in anthracotic "black spots" in the parietal pleura sampled during thoracoscopy from all 14 studied individuals [53]. Chrysotile may undergo not only longitudinal splitting but also breakage into shorter fibers, which may be cleared more readily [18]; however, short chrysotile fibers were reported to prevail in the pleura [48,52].…”
Section: Page -02mentioning
confidence: 93%